Knowledge and Attitude of 2nd Year Medical Students Regarding Post Mortem Examination: A Comparative Study of Two Medical Colleges Situated at Rajasthan - Brijesh Tatwal; Amit Joshi; Sachin Kumar Meena; Sanjay Kumar Jain; Ashok Moondra (Indian Journal of Forensic Medicine and Pathology, 2025)
Context: Autopsy or necropsy means, postmortem examination of a dead body. Post mortem examination is a process which is required to establish the exact cause of death in sudden, suspicious or unnatural cases. In each and every suspicious case, in which police or magistrate needed a complete autopsy is necessary to substantiate the truth of the evidence of eyewitnesses. There are aim and objectives of a autopsy. It determines the mode, manner and time passed since death. In India postmortem examination used to be conducted by graduate doctors. As per New NMC guidelines the undergraduate will be called as IMG (Indian medical Graduate). As per Competency Based Medical Education (CBME) curriculum for undergraduates provided by National Medical Commission (NMC), autopsy is suggestive teaching learning method with autopsy is also a competency. The present comparison was conducted to assess the knowledge and attitude of medical undergraduate students of two medical colleges towards post-mortem as these traits will inÁuence the quality of autopsy reports being preparedbythemin their professional careers. It is very important that the emotions of the students have to be considered while training medical students but unfortunately it is bit neglected since the inception of medical curriculum. These days curriculum also emphasis only on clinical aspect. Material & Method: it is questionnaire-based study. Study was carried out on second year undergraduate medical students of two medical colleges situated at Rajasthan, GMC, Kota & Jhalawar Medical College, Kota. Questionnaires to be answered, were administered to the participating medical students in Google form. Statistical analysis used: For compilation of data, tabulate formation prepared one by one. 162 students of𿿿rst medical college and 46 students of second edical college took part in the study. Conclusion & Results: The undergraduate medical students should be encouraged to observe more autopsies during their study course. Problem-based learning during practical training of autopsy must be incorporated, as a part of the medical curriculum and instead of elective, compulsory rotatory internship training should be there for Forensic Medicine.